Lattice Boltzmann Analysis of Fluid-Structure Interaction with Moving Boundaries (Communications in Computational Physics, 2020)
This work is concerned with the modelling of the interaction of fluid flowwith flexibly supported rigid bodies. The fluid flow is modelled by Lattice-BoltzmannMethod, coupled to a set of ordinary differential equations describing the dynamics ofthe solid body in terms its elastic and damping properties. The time discretization ofthe body dynamics is performed via the Time Discontinuous Galerkin Method. Severalnumerical examples are presented and highlight the robustness and efficiency of theproposed methodology, by means of comparisons with previously published results.The examples show that the present fluid-structure method is able to capture vortex-induced oscillations of flexibly-supported rigid body.